2020
DOI: 10.1002/cnr2.1245
|View full text |Cite
|
Sign up to set email alerts
|

A review of access to cancer facilities in Punjab, Pakistan

Abstract: BackgroundPunjab is the most populous province of Pakistan, with only 12 countries in the world succeeding it in terms of population.AimsThis review article has the objective of providing novel statistics regarding available cancer therapeutics in Punjab across four different sectors—including government, semi‐private, trust and private sectors.Methods and ResultsKeywords such as “cancer treatment,” “facilities,” “Pakistan,” were used to search Pubmed Database. 36 results were generated: after sifting based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…The ratio of medical oncologist to patient is reported to be 0.027 per 100,000 populations with only 21.4% population having access to radiotherapy services in Pakistan. 23 There are various socioeconomic and cultural factors associated in addition to lack of resources in low middle income countries. 24 Poverty has a major role to play and detrimental health impact of growing in a poor family is potentiated by false cultural beliefs they harbor.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of medical oncologist to patient is reported to be 0.027 per 100,000 populations with only 21.4% population having access to radiotherapy services in Pakistan. 23 There are various socioeconomic and cultural factors associated in addition to lack of resources in low middle income countries. 24 Poverty has a major role to play and detrimental health impact of growing in a poor family is potentiated by false cultural beliefs they harbor.…”
Section: Discussionmentioning
confidence: 99%
“…In LMICs like India, there is a disparity in the availability of both external beam radiotherapy and brachytherapy setups, with several large populous states having minimal radiotherapy units [23]. In Pakistan, it is reported that only 22% of the population has access to radiotherapy facilities [24]. In addition, inconsistency in the capping of treatment costs makes it difficult for underprivileged women to access timely treatment.…”
Section: Treatment and Outcomesmentioning
confidence: 99%
“…[20,21] The treatment outcomes for paediatric ALL in Pakistan are subpar because developing countries face a unique set of challenges such as limited access to specialised oncology care units, unavailability of supportive care, nutritional deficiencies, financial constraints and lack of parental education. [22,23] Consequently, patients are more likely to present late with more severe disease or abandon treatment and are more susceptible to infectious complications. [23] Oneweek prednisolone prophase in a cohort of Pakistani children with ALL was useful in stabilising and reducing disease burden.…”
Section: Discussionmentioning
confidence: 99%